2009
DOI: 10.1177/1545968309347681
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Therapeutic and Orthotic Effects of a Foot Drop Stimulator on Walking Performance in Progressive and Nonprogressive Neurological Disorders

Abstract: Subjects with progressive and nonprogressive disorders had an orthotic benefit from FES up to 11 months. The therapeutic effect increased for 11 months in nonprogressive disorders but only for 3 months in progressive disorders. The combined effect remained significant and clinically relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
187
4
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(203 citation statements)
references
References 30 publications
6
187
4
6
Order By: Relevance
“…4 A significant orthotic effect has also been found in a long-term observational study that included a progressive group of 32 people with MS and familial spastic paraplegia. 5 Researchers found a significant improvement in orthotic effect after 3 months of using FES (7%), which was still significant after 11 months (4%). The authors note that many participants did not continue to the end of the study due to the distances involved in traveling to the clinic, which may have influenced the results.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 A significant orthotic effect has also been found in a long-term observational study that included a progressive group of 32 people with MS and familial spastic paraplegia. 5 Researchers found a significant improvement in orthotic effect after 3 months of using FES (7%), which was still significant after 11 months (4%). The authors note that many participants did not continue to the end of the study due to the distances involved in traveling to the clinic, which may have influenced the results.…”
Section: Participantsmentioning
confidence: 99%
“…The existence of an orthotic effect through using FES over a short period is well established. [3][4][5][6] In an initial case series that included 23 people with MS, researchers found a 16% increase in walking speed after 4.5 months of using FES. 3 The findings from the case series were further supported by a two-group randomized controlled trial (N = 44) in which a significant improvement in orthotic effect was found after 12 weeks (6%).…”
mentioning
confidence: 99%
“…Long-term application of FES in combination with weight-supported treadmill training (WSTT) has been shown to improve walking in individuals with SCI [8,[24][25][26]. More recent findings suggest that the therapeutic effect of FES may be mediated by a strengthening of corticospinal connections to ankle dorsiflexor muscles such as the tibialis anterior (TA) [21,27]. There is evidence that repetitive FES alone (i.e., stimulation that is not paired with movement but applied while subjects were seated) can modulate corticospinal circuits controlling ankle dorsiflexion [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…For these applications, FES was designed to directly stimulate peripheral nerves to cause muscle contractions that lead to the muscle conditioning and functional motor output, which have given FES its value as a medical technology. These more immediate effects are referred to as "orthotic" effects [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation